Pemilih Pemula Dalam Pemilu 2024 - Beniman Beniman; Mursin Mursin; Ikbar Ikbar; Chairan Zibar L.Parisu (Jurnal Sultra Elementary School, 2022)
The purpose of this study is to identify the forms of political participation among first-time voters in the 2024 General Election and to determine the factors influencing their political participation. This research employs a qualitative approach with descriptive qualitative analysis techniques. The data used include both primary and secondary data, collected through observation and interviews. The findings reveal that the Simultaneous General Election (Pemilu Serentak) has brought a new dynamic to Indonesia’s democratic process, particularly for first-time voters, as it represents their first opportunity to exercise their voting rights in choosing the President and Legislative Representatives at both regional and national levels. The first simultaneous election was held in 2019, and the upcoming 2024 election marks the next phase in Indonesia’s electoral evolution since the first general election in 1955, which involved over 30 political parties and independent candidates. The 2024 simultaneous election serves as a crucial democratic platform for first-time voters, those who have reached the minimum voting age of 17 since the previous election. It marks an important step in shaping Indonesia’s democratic future and nurturing a generation of informed, active voters. Therefore, first-time voters should be provided with an educational and engaging democratic experience. To enhance their participation, specific strategies and social media campaigns should be utilized to reach and encourage them to actively participate in the democratic process for the sake of the nation’s progress and future.